2014
DOI: 10.1111/hex.12272
|View full text |Cite
|
Sign up to set email alerts
|

Community Engagement in a complex intervention to improve access to primary mental health care for hard‐to‐reach groups

Abstract: Background Despite the availability of effective evidence-based treatments for depression and anxiety, many 'harder-to-reach' social and patient groups experience difficulties accessing treatment. We developed a complex intervention, the AMP (Improving Access to Mental Health in Primary Care) programme, which combined community engagement (CE), tailored (individual and group) psychosocial interventions and primary care involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…Research suggests current approaches may not have enough penetration into the ethnic groups. Alternates via community organisations, media or community champions, needs to be further explored [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests current approaches may not have enough penetration into the ethnic groups. Alternates via community organisations, media or community champions, needs to be further explored [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study identified mental health problems as one main targets for interventions. As individuals in this population are likely to have a complex set of socio-medical problem constellations interventions that base on principles of case management may be promising ( Björkman & Hansson, 2000 ; Gask et al, 2012 ; Lamb et al, 2014 ). Of course, potential future interventions to ameliorate the health of deprived populations and to optimize the use of health resources should be accompanied by scientific evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Although primary mental health care community based in LAMIC has relevant references in the literature 35,40 , there is a gap about this subject in Brazil. Thus, the sub-categories, were developed inductively 41 and fostered the answers to the 3 key-issues of this study.…”
Section: Analysesmentioning
confidence: 99%
“…Due to the fact that the group studied has CMD, mental health stigma 33 and difficulties to accept mental health as a health problem were embedded in these references. Secondly rather than to install a community centre in a vulnerable community, which does not seem enough to a vulnerable population to trust 34 , the literature recommends identifying stakeholders to create service linked to the local people 35,36 . Hence, access to mental health care in a community-based service is a bridge linking the service and community, containing clinical, social, cultural and political elements.…”
Section: Introductionmentioning
confidence: 99%